Spatial Impact of Informal Street Vending Structures on the Public Space; [Impacto Espacial de Las Estructuras Humanas del Comercio Callejero Informal Sobre el Espacio Público] - Margarit-Segura, D (Universidad Austral de Chile, 2024)
Informal street vending moves affections, emotions, knowledge, objects, merchandise, money, and/or artifacts, and is produced and reproduced in the city’s public space. In this context, -fixed or mobile- vending stands have an impact on a city’s public spaces. This article presents an comparative analysis -before and during the COVID-19 pandemics- of the spatial impact of informal street vending in Valparaíso, Chile. For this purpose, we focus on what we have called human street vending structures, understood as systems made up by the traders’ bodies and all the objects that conform their vending stands. The results revealed that, during the pandemics, street trade increased by 133%, and human structures tended to improve and even enlarge their stands. © (2024), (Universidad Austral de Chile). All Rights Reserved.